Industry Collaboration Program (ICP): Empowering Technology Development for National Economic Growth - Abdullah, A.; Safari, Z. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Malaysia is currently aiming to become a developed nation by year 2020. In doing so, Malaysia leverages on many platforms/programs to achieve the goals. Malaysia needs to be aggressive in moving forward in particular in the area of technology and economy development to stay as a competitive economy globally. The New Economic Model (NEM) introduced aims to create high income society, sustainability and inclusiveness which lead to high quality of life. Therefore, Malaysia needs to further develop the required capability and capacity in particular related to technology as a catalyst to leap-frog the nation to become a knowledge-based economy. Apart of having long term development plans such as the New Economic Model, Industrial Master Plan, the Five-Year-Plan and Science & Technology Policy, the Government is currently exploring another platform namely the Industrial Collaboration Program (ICP). It is envisaged that the ICP platform is able to create ‘value for money’ in forms of economic returns based on the procurement made by the Government. It is capitalized to further enhance national local technology capacity and capability development activities by ensuring participation of local resources in high technology sectors, such as transportation and security; with the aim to create employment, skills enhancement and technology development capability within the local firms.